Kualitas Hidup pada Penyintas Skizofrenia di Wilayah Perkotaan - Chaimira, Sausandha Yasma; Widianti, Efri; Susanti, Raini Diah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to discuss the quality of life of schizophrenia survivors in urban areas. The research method used is quantitative descriptive. The results showed that (57.1%) respondents had a high quality of life and (42.9%) respondents had a low quality of life. Based on the 8 dimensions of SQol, the results showed that the dimension with the highest average quality of life was the Relationship with Family dimension (87.143). Meanwhile, the lowest quality of life is the Sentimental Life Dimension (53.492). In conclusion, the quality of life of schizophrenia survivors in urban areas mostly has a high quality of life. Keywords : Quality of Life, Schizophrenia